The Effect of Fomo, Perceived Scarcity, and Price Discounts on Impulse Buying Behavior in Tiktok Shop (International Journal of Economics and Management Research, 2026)
This study aims to analyze the influence of Fear of Missing Out (FOMO), perceived scarcity, and price discounts on impulsive buying behavior among TikTok Shop users in Banyumas Regency. Impulsive buying behavior is often triggered by digital marketing strategies that emphasize urgency, viral trends, and limited-time offers. This research employed a quantitative approach with a survey method. Data were obtained through an online questionnaire distributed to 140 respondents who are active TikTok Shop users residing in Banyumas Regency. The sampling technique used was purposive sampling with the criteria that respondents had made    purchases within the last six months. Data were analyzed using multiple linear regression. The results showed that FOMO had a positive and significant effect on impulsive buying behavior, perceived scarcity had a positive and significant effect on impulsive buying behavior, and price discounts also had a positive and significant effect on impulsive buying behavior. Simultaneously, these three variables contributed to encouraging impulsive buying behavior among TikTok Shop consumers in Banyumas Regency. These findings are expected to provide insights for making more prudent purchasing decisions.